Effect of tetrandrine on myocardial Na+, K(+)-ATPase in renovascular hypertensive rats - Chen Nian-hang; Wang You-lin; Ding Jian-hua (Acta Pharmacologica Sinica, 2016)
In renovascular hypertensive rats (RVHR, two-kidney, one-clip model), the myocardial Na+, K(+)-ATPase showed a reduced activity. Though its sensitivities to K+ and ouabain (Oua) were not changed, the enzyme was less responsive to Na+ and ATP, and also much more susceptible to the inhibitory effect of Ca2+. Tetrandrine (Tet, ig 50 mg.kg-1, qd x 26 d) increased the myocardial Na+, K(+)-ATPase activity in RVHR. However, in vitro, Tet elevated moderately the enzyme activity in RVHR only at high concentrations (100-1,000 mumol.L-1), and failed to influence the enzyme activity in normotensive rats. In RVHR, treatment by Tet in vivo increased the degree of the Na+, K(+)-ATPase activation under suboptimal substrate (Na+, K+, or ATP) concentrations and antagonized the inhibitory effect of Ca2+ or Oua. Similar results were found when the enzyme preparation from RVHR was incubated with Tet 10 mumol.L-1 during ATPase analysis. On the contrary, the myocardial Mg(2+)-ATPase activity was higher in RVHR. Tet depressed this enzyme both in vivo and in vitro. These facts indicate that the increased myocardial Na+, K(+)-ATPase activity in RVHR is not only secondary to the calcium channel blocking or antihypertensive action of Tet but also due to its direct effects on the Na+, K(+)-ATPase and Mg(2+)-ATPase.